The effects of depression, stress, and somatization on clinical prognosis and treatment in patients suspicious of benign prostatic hyperplasia - Muhammad Sarim Khan , Muhammad Yawar Mushtaq, Usama Shoukat, Nauman Ahmed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aim: It was the first research to study how depression, stress, and somatoform disorder affect therapy reply for lower urinary tract symptoms (LUTS), suspicious of benign prostatic hyperplasia (BPH). Method: Respondent Health Questionnaire-9,7- item Sweeping Nervousness Syndrome Scale, and PHQ 17 are being used to assess LUTS/BPH individuals. The main result was just the responder’s rate, which was defined as total IPSS score (6) at the conclusion of therapy. Results: The intensity of LUTS/BPH was considerably greater in people experiencing sadness (p value = 0.025; storage sub-sign (p value = 0.023) or else somatization (p value = 0.026) than in these deprived of, although standard of living remained higher for cases experiencing anxiousness (p value = 0.039) than that of other deprived of. Nervous participants had a substantially larger number of non than those who were not (odds ratios [OR], 4.295, P = 0.023), whereas somatic respondents had the tendency to have greater non-responders (OR, 4.553, p value = 0.068). Our preliminary findings imply that sadness, anxiety, and somatic complaints might have had an impact on treatment manifestations of LUTS/BPH. Furthermore, apprehensive individuals with LUTS/BPH exhibited a worse response to therapy. Conclusion: Despite its drawbacks, the current study shows that doctors may also need to conduct a detailed examination of psychotic features in order to successfully manage individuals suffering LUTS/BPH.